Direct Health Care Costs Associated With Multiple Sclerosis: A Population-Based Cohort Study in British Columbia, Canada, 2001–2020. (28th February 2023) - Khakban, Amir; Rodriguez Llorian, Elisabet; Michaux, Kristina D.; Patten, Scott B.; Traboulsee, Anthony; Oh, Jiwon; Lynd, Larry D.
Abstract : Background and Objectives: Multiple sclerosis (MS), a leading cause of nontraumatic neurologic disability in young adults, exerts a substantial economic burden on the health care system. The objective of this study was to quantify the excess health care costs of MS in British Columbia, Canada. Methods: A retrospective-matched cohort study of patients with MS was conducted using population-based administrative health data from 2001 to 2020. Patients with MS who satisfied a validated case definition were matched to 5 unique controls without MS on sex, age, and cohort entry date. Patients and controls were followed to the end of 2020 or to their last health care resource use, whichever came first. We calculated the direct medical costs for each individual, including outpatient services use, hospital admissions, and dispensed medications. We used generalized linear models with an identity link and normal distribution to estimate the excess cost of MS as the mean cost difference between patients with MS and controls. All costs were reported in 2020 Canadian dollars. Results: A total of 17, 071 patients with MS were matched to 85, 355 controls. Overall, 72.4% were female, and the mean age at cohort entry date was 46.1 years. The excess cost of MS was $6, 881 (95% CI: $6, 713, $7, 049) per patient-year. Inpatient, outpatient, and medication costs accounted for 25%, 10%, and 65% of excess costs, respectively. Excess costs were higher in patients with MS with at least one disease-modifying therapy (DMT) prescription ($13, 267; 95% CI: $12, 992–$13, 542) compared with non-DMT users ($3, 469; 95% CI: $3, 297–$3, 641) and even higher among frequent DMT users ($24, 835; 95% CI: $24, 528–$25, 141). Patients with MS with a history of at least one relapse requiring hospitalization had higher excess costs ($10, 543; 95% CI: $10, 136–$10, 950) compared with patients with MS without a relapse; hospitalizations accounted for 51% of the costs in this group. The excess cost of hospitalizations was $1, 391 lower among frequent DMT users than non-DMT users. Discussion: The economic burden of MS is considerable, with medications, particularly DMTs, being the largest cost driver. Future studies should investigate how disease management strategies, including early diagnosis and timely use of DMTs, could offset future and ongoing costs while improving patients' quality of life.